A sílaba na relação com a escrita: ataques ramificados na escrita de crianças dos segundo e quarto anos – um estudo a partir do EFFE-On - Pampim, Moisés; Reis, Diana; Mendonça, Cristiana; Fernandes, Iolanda (Revista da Associação Portuguesa de Linguística, 2019)
The syllable is a unit of the phonological system of human languages that has been the subject of numerous studies in language and language acquisition. Using longitudinal data from the online corpus EFFE-On, this article focuses on the evaluation of children's written performance with respect to the order of acquisition of the syllable structure, in particular the analysis of branching Onsets (obstruent+liquid). The study focuses on the performance of second and fourth graders in the Lisbon area and will allow us to describe the relationship between phonological and orthographic knowledge in children attending the first years of elementary education.